Pengaruh Alokasi Dana Desa Dan Pengembangan BUMDes Terhadap Peningkatan Kesejahteraan Masyarakat - Anti Ibrahim; Syarwani Canon; Sudirman Sudirman (State University of Gorontalo, 2023)
This research aims to determine the influence of Village Fund Allocation and BUMDes development on the improvement of the community welfare in Ilomata Village, Atinggola Subdistrict, North Gorontalo Regency. This research employs a quantitative approach with a descriptive quantitative method and a total sample of 47 participants. The data are collected through observation, questionnaire, interview, and documentation, with the data analysis employing Multiple Linear Regression. In conformity with the research finding, the Village Fund Affocation and BUMDes development positively influence the improvement of the Contity welfare in Ilomata Village, Atinggola Subdistrict, North Gorontalo Distriel